Computational Viscoelasticity - Marques, Severino P. C.; Creus, Guillermo J. (SpringerBriefs in Computational Mechanics,, 2012)
This text is a guide how to solve problems in which viscoelasticity is present using existing commercial computational codes. The book gives information on codes' structure and use, data preparation  and output interpretation and verification. The first part of the book introduces the reader to the subject, and to provide the models, equations and notation to be used in the computational applications. The second part shows the most important Computational techniques: Finite elements formulation, Boundary elements formulation, and presents the solutions of Viscoelastic problems with Abaqus.